2022
DOI: 10.1200/jco.2022.40.16_suppl.e15581
|View full text |Cite
|
Sign up to set email alerts
|

Real-world outcomes among patients with metastatic colorectal cancer treated first line with bevacizumab-awwb.

Abstract: e15581 Background: Bevacizumab-awwb (MVASI) was the first FDA-approved biosimilar to Avastin (reference product, RP). Real-world data on effectiveness and safety remain limited and may help address barriers to utilization. Methods: Adult patients who had a confirmed diagnosis of metastatic colorectal cancer (mCRC) (initial presentation on or after 1 January 2018) and initiated bevacizumab-awwb between 19 July 2019 and 30 April 2020 were identified in the ConcertAI Definitive Oncology EMR Dataset. A retrospect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…In the 2023 study conducted by Jin et al 17 the experimental group had an average success rate of 87.6% compared with the control group's 71.4%. This represented the notable difference of 16.2%, indicating that the intervention had significant effect.…”
Section: Resultsmentioning
confidence: 95%
See 3 more Smart Citations
“…In the 2023 study conducted by Jin et al 17 the experimental group had an average success rate of 87.6% compared with the control group's 71.4%. This represented the notable difference of 16.2%, indicating that the intervention had significant effect.…”
Section: Resultsmentioning
confidence: 95%
“…The comprehensive summary of studies that investigated treatments for mCRC, with an emphasis on bevacizumab and its biosimilars revealed that Jin et al 17 assessed the efficacy of bevacizumab‐awwb treatment in adult patients with mCRC. Their primary outcomes were thromboembolic and hemorrhagic events, but none of these resulted in fatalities.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations